Legal Research on The Return of State Financial Losses Through Additional Punishment of Restitution Payments Based on Judge's Consideration (Comparative Study Between Indonesia and South Africa) - Jaco Barkhuizen; Singgih Purnomo; Rina Arum; Dr. Du Ngoc Bich (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Purpose of the study (Tujuan): This study aims to ascertain the judge's consideration in determining additional punishment and describe the problematic implementation of the judge’s consideration (Comparative study of Indonesia and South Africa). Methodology:This study’s type is normative juridical legal research. This approach was employed to obtain a description of the analysis of legal regulations governing restitution as an additional punishment for corruption offenses. The case approach is normative juridical research aimed at studying the application of legal norms or rules carried out in legal practice. Concerning this research, the example of a case to be studied was a corruption case with permanent legal force, namely the Corruption Court Decision (Comparative study between Indonesia and South Africa). Primary data were specifically gathered to answer research questions by interview method. The data analysis technique utilized was a qualitative analysis technique using the interactive method. Results:Based on the results of the aforementioned research, 1) South Africa uses the asset recovery system and involves third parties. In corruption cases in South Africa, the courts seek to ensure that money lost due to corruption is returned to the state. On February 25, 2019, the president of South Africa announced that a special court would be established in accordance with section 2 (1) of the Special Investigative Units and Courts Act, Act No. 74 of 1996, to hear cases arising in court proceedings. 2) In Indonesia, judges have obstacles in interpreting Article 18 of Law No. 31 of 1999 on Corruption Crime Law. The additional restitution punishment is regulated in Article 18 of Law Number 31 of 1999, and the general explanation states,